2002
DOI: 10.1046/j.1365-313x.2002.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane oxidase NtrbohD is responsible for AOS production in elicited tobacco cells

Abstract: ). ² These authors contributed equally to this work. SummaryA cDNA encoding a protein, NtrbohD, located on the plasma membrane and homologue to thē avocytochrome of the neutrophil NADPH oxidase, was cloned in tobacco. The corresponding mRNA was accumulated when tobacco leaves and cells were treated with the fungal elicitor cryptogein. After elicitation with cryptogein, tobacco cells transformed with antisense constructs of NtrbohD showed the same extracellular alkalinization as the control, but no longer produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(210 citation statements)
references
References 57 publications
8
201
1
Order By: Relevance
“…ROS production induced in tobacco cells by cryptogein is due to a plasma membrane NADPH oxidase, NtrbohD (Simon-Plas et al, 2002). In this study, we show that transgenic cells inactivated for NtrbohD do not present cryptogeinstimulated clathrin endocytosis, although some other signaling events triggered by the elicitor, such as extracellular alkalinization, are identical to those observed in wild-type cells.…”
Section: Ros Production Is Correlated With Endocytosismentioning
confidence: 54%
See 2 more Smart Citations
“…ROS production induced in tobacco cells by cryptogein is due to a plasma membrane NADPH oxidase, NtrbohD (Simon-Plas et al, 2002). In this study, we show that transgenic cells inactivated for NtrbohD do not present cryptogeinstimulated clathrin endocytosis, although some other signaling events triggered by the elicitor, such as extracellular alkalinization, are identical to those observed in wild-type cells.…”
Section: Ros Production Is Correlated With Endocytosismentioning
confidence: 54%
“…A BY-2 cell line (named gp3) was previously obtained expressing an antisense construction of NtrbohD cDNA, which is unable to produce ROS when treated with cryptogein, but still responds to the elicitor by an increase in extracellular pH (Simon-Plas et al, 2002) and membrane depolarization (this study; data not shown), similar to wild-type cells.…”
Section: Cryptogein-stimulated Clathrin Endocytosis Is Inhibited In Cmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, molecular biology approaches led to the discovery of flavocytochromes of the FRO family that use cytosolic pyridine nucleotides to reduce apoplastic ferrichelates (Robinson et al, 1999). Structurally similar flavocytochromes (Rboh) are involved in one-electron reduction of oxygen with production of superoxide (Simon-Plas et al, 2002). However, these plant flavocytochromes apparently account for a very minor portion of b-type cytochromes associated with the PM, at least under unstressed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, expression of an NADPH oxidase gene (NtRbohD) was also suppressed at 30 u C in TMV-inoculated leaves. NtRbohD encodes an NADPH oxidase shown to be involved in ROS production in tobacco cells treated with the fungal elicitor cryptogein (Simon-Plas et al, 2002). It is likely that the decrease in levels of O 2 $ 2 detected at 30 u C is, at least in part, a consequence of decreased NADPH oxidase gene expression and activity.…”
Section: Discussionmentioning
confidence: 99%